Fatigue Strength of X45CrSi93 stainless steel applied as internal combustion engine valves - Voorwald, Herman Jacobus Cornelis [UNESP]; Coisse, R. C.; Cioffi, M. O. H. (Elsevier B.V., 2011)
Stainless steels are used to intake and exhaust valves production applied as internal combustion engines. In general valves are requested to support cyclic stresses applied due to opening and closing processes during the operation. The objective of this research is to study the influence on the axial fatigue strength of the resulting microstructure after heat treatment at the martensitic X45CrSi93 steel, combined with different surface treatments as hard chrome-plating, nitride and grinding. It was verified a significant increase on the fatigue strength of the martensitic steel after nitriding, compared with results from the chrome-plating specimens. A slight increase in the tensile strength was also noticed on nitrided parts as a consequence of a resistance increase due to nitrogen and carbon solid solution. (C) 2011 Published by Elsevier Ltd. Selection and peer-review under responsibility of ICM11
Keywords: stainless steels; valves; nitride; fatigue